Faktor-faktor mempengaruhi pengurusan risiko, dalam kalangan Penolong Pegawai Perubatan/ Jururawat di Jabatan Psikiatri, Hospital Raja Perempuan Zainab II - Mohd Awal Din, Mohd Nazir (2020)
Risk management play a crucial role for optimizing resource, to reducing the course and compensation. It’s also reflected of organisation achievement and reputation. This study purposely to identify factor that contribute to the efficiency risk management. In this study attention given to commitment management, training and safety communication. This study applies the questionnaire for data collection and involved 57 respondents. The data was analysed by using Statistical Package for Social Sciences (SPSS) version 25. Colleration analysis shown that commitment management, training and safety communication has strong relationship with efficiency risk management. Furthermore, the multiple regration analysis revealed that only safety training has significantly contributed toward risk management efficiency. 45.4% of the risk management efficiency was explained by safety training. Thus, safety training needs to be taken account for risk management improvement programme. This study was discussed about the finding of study, the limitation of study and suggestion for improvement in the future study.